Konservasi Lahan Marjinal Dengan Aplikasi Biochar Plus - Ikhsan Hasibuan (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2017)
In our country, marginal land occupy for about 50 million hectares or almost one forth of total land. In Sumatra, nearly all marginal land is dominated by podzolik soil which about 10 million hectares. The main problems of this soil are including low pH, high Al content, low cation exchange capacity, and poor of nutrient and organic matter level, therefore the growth and yield of plants can not be optimal. Traditionally, farmers use lime to solve this problem, but this method only influences the chemical aspect but not the biological one. The solution we offer in research is by applying biochar. It is high in carbon, porous and could improve soil fertility. This research aimed to know and evaluate the impact of biochar application on growth and yield of corn. The result showed that biochar gave positive impact on growth and yield of corn. By using biochar the corn height reached 155,67 cm while applying lime could only grew till 56 cm and 20 cm by using no ameliorant or control. Furthermore, the corn seed weight was thrice by biochar than by lime that were 194,5 g compared to 42 g per plant. Meanwhile, the corn plants were failed to produce yield in treatment of chemical fertiliser and control.